การพัฒนาความสามารถในการสื่อสารภาษาจีนโดยประยุกต์ใช้บอร์ดเกมร่วมกับ ชุดแบบฝึกการสื่อสาร ของนักเรียนชั้นมัธยมศึกษาปีที่ 5 วิชาเอกภาษาจีน - เหลืองธนกุล ปัญจรส (วารสารวิจัยทางการศึกษา คณะศึกษาศาสตร์ มหาวิทยาลัยศรีนครินทรวิโรฒ, 2021)
บทคัดย่อ การวิจัยครั้งนี้มีจุดประสงค์เพื่อ 1) พัฒนาบอร์ดเกมและชุดแบบฝึกการสื่อสาร สำหรับนักเรียนชั้นมัธยมศึกษาปีที่ 5 วิชาเอกภาษาจีน โรงเรียนสาธิต มศว ประสานมิตร (ฝ่ายมัธยม) 2) ศึกษาผลการประยุกต์ใช้บอร์ดเกมร่วมกับชุดแบบฝึกการสื่อสาร สำหรับนักเรียนชั้นมัธยมศึกษาปีที่ 5 วิชาเอกภาษาจีน โรงเรียนสาธิต มศว ประสานมิตร (ฝ่ายมัธยม)โดยมีวัตถุประสงค์ย่อย ดังนี้ 2.1) เปรียบเทียบความสามารถในการสื่อสารภาษาจีน ระหว่างก่อนและหลังการใช้บอร์ดเกมร่วมกับชุดแบบฝึกการสื่อสาร2.2) ศึกษาความพึงพอใจของนักเรียนที่มีต่อการประยุกต์ใช้บอร์ดเกมร่วมกับชุดแบบฝึกการสื่อสาร กลุ่มเป้าหมายที่ใช้ในการวิจัยครั้งนี้ คือ นักเรียนชั้นมัธยมศึกษาปีที่ 5 วิชาเอกภาษาจีน โรงเรียนสาธิต มศว ประสานมิตร (ฝ่ายมัธยม) ภาคเรียนที่ 2 ปีการศึกษา 2562 จำนวน 25 คน เครื่องมือที่ใช้ในการวิจัย ได้แก่ บอร์ดเกม ชุดแบบฝึกการสื่อสาร แบบประเมินทักษะการสื่อสารภาษาจีน และแบบสอบถามความพึงพอใจ วิเคราะห์ข้อมูลโดยการหาค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน และ t-test for dependent sample ผลการวิจัยพบว่า 1) บอร์ดเกมและชุดแบบฝึกการสื่อสารที่พัฒนาขึ้นมีคุณภาพ เนื่องจากผ่านการประเมินจากผู้เชี่ยวชาญ พบว่า บอร์ดเกมและชุดแบบฝึกการสื่อสาร ทุกชุดทั้ง 6 ชุด เหมาะแก่การนำไปใช้ในการจัดการเรียนรู้ในระดับมาก 2) ความสามารถในการสื่อสารของนักเรียนที่ได้รับการสอนโดยใช้บอร์ดเกมร่วมกับชุดแบบฝึกการสื่อสารหลังเรียนสูงกว่าก่อนเรียนอย่างมีนัยสำคัญทางสถิตที่ระดับ 0.53) นักเรียนมีความพึงพอใจต่อการใช้บอร์ดเกมร่วมกับชุดแบบฝึกการสื่อสารอยู่ในระดับมาก (.= 4.39, S.D. = .32) คำสำคัญ: การประยุกต์ใช้บอร์ดเกมร่วมกับชุดแบบฝึกการสื่อสาร; ความสามารถในการสื่อสารภาษาจีน; ความพึงพอใจของนักเรียนที่มีต่อการประยุกต์ใช้บอร์ดเกมร่วมกับชุดแบบฝึกการสื่อสาร ABSTRACT The objectives of this research were 1) to develop board game with Chinese writing and reading exercises for communication skill development of Chinese Major MatthayomSueksa 5 students at Srinakharinwirot University Prasarnmit Demonstration Secondary School, 2) to study the effect of the application of board game with Chinese writing and reading exercises for communication skill development of Chinese Major MatthayomSueksa 5 students at Srinakharinwirot University Prasarnmit Demonstration Secondary School, with sub-objectives 2.1) to compare Chinese communication ability between before and after implementing the developed board game with Chinese writing and reading exercises, and 2.2) to study students’ satisfaction with the developed board game with Chinese writing and reading exercises. The sample participants of this research is twenty-five Chinese Major MatthayomSueksa 5 students at Srinakharinwirot University Prasarnmit Demonstration Secondary School during second semester (2/2019). The research tools are as follows: a board game, Chinese writing and reading exercises for communication skill, a Chinese communication skill assessment form, and a satisfaction survey form. The data was analyzed by finding the mean (), standard deviation (SD), and t-test for dependent sample. The results of this research indicated as follows: 1) the developed board game with Chinese writing and reading exercises for communication skill development of Chinese Major MatthayomSueksa 5 students at Srinakharinwirot University Prasarnmit Demonstration Secondary School was efficient. Examined by experts, all 6 board games were highly suitable for implementing for learning management. 2)after implementing the developed board game with Chinese writing and reading exercises, Chinese communication achievement of the sample students was higher than before with a statistical significance level of 0.5, and 3) the sample students were highly satisfied with the developed board game with Chinese writing and reading exercises for self-development in Chinese communication. (.= 4.39, S.D. = .32) Keywords: Effect of the application of board game with Chinese writing and reading exercises for communication skill; Chinese communication ability; Students’ satisfaction with the developed board game with Chinese writing and reading exercises